The relationship between workers' experience and productivity: a case study of brick masonry construction. Issue 4 (12th March 2023) - Khanh, Ha Duy; Kim, Soo-Yong; Khoa, Nguyen Van; Tu, Nguyen Thanh
Abstract: For decades, extensive studies have investigated significant factors affecting the construction's labor productivity. However, it is always necessary to qualify and forecast the construction productivity using novel methods. Based on the criticism on the comprehensive literature review, this study found that the genuine relationship between workers' qualifications and construction productivity has not been recognized and modeled. Therefore, for this paper, the input data had been collected through a structured questionnaire together with the work sampling method and was then analyzed by statistical tools. The results showed that the real productivity for the 110 mm wall is less than the baseline productivity, whereas that of the 220 mm wall is higher than the baseline productivity. In addition, there is no difference in the actual productivity of brick masonry construction between worker's experience groups, whereas it is a significant difference between worker's skill groups. Based on the binary logistic regression, this study has developed a model to correctly predict the productivity for masonry work of two brick walls based on worker's experience and skill. The analysis results indicated that this performance could be obtained with the minimum and maximum correct percentage of approximately 40% and 98%. Eventually, this study proposes two useful ways to improve the skills of masonry workers so that they can accelerate construction productivity.